The rs2237892 Polymorphism in KCNQ1 Influences Gestational Diabetes Mellitus and Glucose Levels: A Case-Control Study and Meta-Analysis - Ao, Deng (PLoS One, 2015)
OBJECTIVE: Recent genetic studies have shown that potassium voltage-gated channel, KQT-like subfamily, member1 (KCNQ1) gene is related to gestational diabetes mellitus (GDM). However, studies for the rs2237892 polymorphism in KCNQ1 and GDM remain conflicting in Asians. Furthermore, associations of this polymorphism with glucose levels during oral glucose tolerance test (OGTT) have not been described in Chinese pregnant women. The present study aimed to provide evidence for the associations of rs2237892 in KCNQ1 with GDM and glucose levels, and to systematically evaluate the effect of rs2237892 on GDM in Asians. METHODS: A case-control study on 562 women with GDM and 453 controls was conducted in Beijing, China. The association of rs2237892 with risk of GDM was analyzed using logistic regression. The associations with quantitative glucose levels were assessed using linear regression models. A meta-analysis including the present case-control study and four previously published reports in Asians was conducted. RESULTS: The rs2237892 polymorphism in KCNQ1 was associated with GDM (OR (95%CI) =1.99(1.26-3.15)). Additionally, the polymorphism was associated with levels of 1h and 2h glucose during OGTT. The pre-pregnancy BMI, age and genotypes of KCNQ1 polymorphism were independent risk factors of GDM. Subsequently, we performed a meta-analysis in Asians. In total, C-allele carriers of rs2237892 polymorphism had a 50% higher risk for GDM (OR (95%CI) =1.50(1.15-1.78)). CONCLUSION: The study demonstrated for the first time that the KCNQ1 rs2237892 polymorphism was associated with GDM and glucose levels in Chinese women. The study provides systematic evidence for the association between this polymorphism and GDM in Asians.